2008
DOI: 10.1152/ajpgi.00074.2008
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in human NAFLD

Abstract: Despite the high prevalence of nonalcoholic fatty liver disease (NAFLD), little is known of its pathogenesis based on study of human liver samples. By the use of Affymetrix GeneChips (17,601 genes), we investigated gene expression in the human liver of subjects with extreme steatosis due to NAFLD without histological signs of inflammation (liver fat 66.0 +/- 6.8%) and in subjects with low liver fat content (6.4 +/- 2.7%). The data were analyzed by using sequence-based reannotation of Affymetrix probes and a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
266
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(303 citation statements)
references
References 63 publications
20
266
3
6
Order By: Relevance
“…31,37 Recently, it was reported that abnormal upregulation of CD36 on the plasma membrane of hepatocytes contributes to hepatic fat accumulation, insulin resistance, and hyper-insulinemia in patients with NAFLD. 38,39 Consistent with these reports, the hepatic mRNA and protein levels of PPAR-g and CD36 were abnormally elevated, and hyperglycemia and hyperinsulinemia were also observed in HFD-fed mice (Figures 6a-c and Table 3), confirming that the PPAR-g-signaling pathway and CD36 are involved in HFD-induced NAFLD. Our data also clearly showed high levels of CYP2E1 mRNA expression and lipid peroxidation products in the livers of HFD-fed mice (Figures 3a and b).…”
Section: Discussionsupporting
confidence: 83%
“…31,37 Recently, it was reported that abnormal upregulation of CD36 on the plasma membrane of hepatocytes contributes to hepatic fat accumulation, insulin resistance, and hyper-insulinemia in patients with NAFLD. 38,39 Consistent with these reports, the hepatic mRNA and protein levels of PPAR-g and CD36 were abnormally elevated, and hyperglycemia and hyperinsulinemia were also observed in HFD-fed mice (Figures 6a-c and Table 3), confirming that the PPAR-g-signaling pathway and CD36 are involved in HFD-induced NAFLD. Our data also clearly showed high levels of CYP2E1 mRNA expression and lipid peroxidation products in the livers of HFD-fed mice (Figures 3a and b).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the ND-diet induced a marked increase of expression of genes encoding proteins responsible for FFA uptake, binding and transport (Cd36, Fabp1), whereas the expression of genes involved in FA (de novo) synthesis (Acaca, Fasn, Scd1) were only slightly increased. These findings are similar as described in NASH patients 26,33 and indicate that significantly higher FFA levels in ND-fed mice compared with control mice (31.4 ± 2.7 vs 23.9 ± 2.4 mEq/g protein; P ¼ 0.007) are mainly caused by enhanced hepatic FFA uptake. Similar to human NASH, 34 ND-feeding lead to a significant upregulation of expression of genes involved in mitochondrial (Acadl, Cpt1), peroxisomal (Acox1) and microsomal (Cyp2e1, Cyp4a10) FFA oxidation, which are known to cause increased reactive oxygen species (ROS) formation.…”
Section: Effect Of the Nd On Obesity And Other Elements Of The Metabosupporting
confidence: 88%
“…In addition to subsystems previously implicated in NASH (for example, folate, vitamin B6, lipid, eicosanoid and amino acid metabolism 40,41 ), new Reporter Metabolites involved in glycan metabolism and biosynthesis of chondroitin sulphate (CS), a proteoglycan (PG) were identified. Previously, the association of serum levels of hyaluronic acid (a non-sulphated glycosaminoglycan) with the fibrosis stage in chronic liver diseases, including NAFLD, was reported 28,42 .…”
Section: Article Nature Communications | Doi: 101038/ncomms4083mentioning
confidence: 99%